PENERAPAN KONSEP HUMAN RELATION PIMPINAN DALAM MENINGKATKAN KUALITAS PELAYANAN (STUDI PADA PT. PERSERO JASA RAHARJA CABANG SULTRA) - Ningsih, Siska Rahayu; Tarifu, La; Taufik, Taufik (REZ PUBLICA, 2020)
This research aims to know and describe the application of human relation leadership in PT. Persero Jasa Raharja Sultra Branch, to know and describe the quality of service at PT. Persero Jasa Raharja Sultra Branch. The research method used in this research is a qualitative descriptive, the informant in this research is head of chairman of PT. Persero Jasa Raharja Sultra Branch, Mobile Service PT. Persero Jasa Raharja Sultra Branch, 3 people as Additional informen. Primary and secondary data sources. Technical interview, observation and documentation. While the data analysis techniques used in qualitative descriptive research. The results showed that the application of human relation leadership of PT. Persero Jasa Raharja Sultra Branch is considered not good enough. The implementation of the human relation leadership concept has not been fully implemented, where the level of implementation can be seen from several dimensions, namely: (1) communication (2) motivation (3) responsibility (4) empathy. Through the implementation of human relation of leadership in PT. Persero Jasa Raharja Sultra Branch is considered not yet able to encourage in improving the quality of service to the community. The quality of service has not been carried out completely, so it is considered not good enough, where the quality of service indicators consist of: (1) effective (2) simple (3) openness (4) responsive.